A Critical Analysis of Legal Research in Kenya: The Nexus between Research Funding, Academic Freedom and Social Responsibility. (July 2018) - Meroka, Agnes K.; Ojwang, Duncan
Despite the potential of legal research to contribute positively in addressing problems in the society, there are various factors that can undermine the significance of such research. Even with the widespread legal research conducted in Kenya, there are signs that much of this research has not had a significant impact in the society, and it has also not succeeded in providing solutions to some of the problems that have been plaguing the country since the post-independence period. It is argued here that academic freedom, like any other fundamental freedom or right has obligations attached to it, and one such obligation is the exercise of social responsibility, which means that research ought to be conducted for the purpose of benefitting the society and not just for the advancement of individual interests. However, external research funding may limit the extent to which academics are able to exercise academic freedom in the course of conducting research. In Kenya specifically, the Constitution of Kenya recognizes and protects academic freedom, however, the spiral relationship between research and external funding opportunities may create conditions which undermine this freedom. This article draws on a broad understanding of the role of legal research in any society and demonstrates that there is a need for independence of thought in carrying out legal research, and in cases where external research funding threatens the exercise of academic freedom, universities can take steps to ensure that individual academics are cushioned from this threat.